2017
DOI: 10.1186/s13037-017-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the “Bone-Screw-Fastener” for improved screw fixation in orthopedic surgery: a revolutionary paradigm shift?

Abstract: BackgroundConventional screws used for fracture fixation in orthopedic surgery continue to rely on the historic buttress thread design. While buttress screws generally provide solid resistance against unidirectional axial loading forces, their design suffers from several limitations, as the buttress thread does not adequately resist multiaxial forces. Furthermore, the buttress screw is prone to stripping at the bone-screw interface and can cause microfracturing of the surrounding bone due to its thread design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…The proposed advantages of the interlocking thread design include improved resistance to multidirectional forces and improved resistance to stripping. 22 This hypothesis is supported by a recent study that demonstrated that ITS has higher torque stripping resistance than BTS. 42 Further studies are required to determine how the increased temperature and work generated during drilling and screw insertion impacts the ITS performance in a clinical setting.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The proposed advantages of the interlocking thread design include improved resistance to multidirectional forces and improved resistance to stripping. 22 This hypothesis is supported by a recent study that demonstrated that ITS has higher torque stripping resistance than BTS. 42 Further studies are required to determine how the increased temperature and work generated during drilling and screw insertion impacts the ITS performance in a clinical setting.…”
Section: Discussionmentioning
confidence: 69%
“…The multidirectional thread pattern is also theorized to better resist multidirectional loads and better distribute loading forces across all thread surfaces compared to conventional buttress thread screws. 22 A proprietary drill bit whose drill point angles and drill body design differ from those of standard surgical drill bits was developed in conjunction with the ITS. Design changes were intended to improve clearance of bone debris from the drill hole and thus optimize the screw bone interface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osteonecrosis potentially results in catastrophic failures of orthopaedic screw-bone constructs and sometimes even promotes infection [7]. In summary, the essential shortcomings of buttress threads include the risk of stripping, screw loosening, induction of stress risers, bone micro-fracturing, heat necrosis, with subsequent failure of fixation and risk of creating fracture nonunions and malunions [8]. In the field of articular cartilage repair, bone marrow stimulation is often performed using either a surgical twist drill bit or a Kirschner wire to introduce defined holes in the subchondral bone plate following meticulous removal of the calcified cartilage layer at the bottom of the defect.…”
Section: Osteonecrosis: View From Abovementioning
confidence: 99%